The Role of Parents' Secure Attachment Towards the Independence of Children Aged 4-5 Years at Wolowa Baru Kindergarten, Wolowa District, Buton District - Apryani Apryani; La Jeti (AIQU: Journal Multidiscipliner of Science, 2023)
This study aims to describe the role of parents' secure attachment on the independence of children aged 4-5 years in the New Wolowa Kindergarten. This research uses a qualitative descriptive approach with the subjects of this research being students and their parents (mothers) in group A aged 4-5 years at the end of the first and second semesters of the 2021/2022 academic year. This research uses data collection techniques in the form of observation, interviews, documentation. With observation subjects totaling 7 children. Data analysis uses data reduction analysis techniques, data display, and drawing conclusions. So the results of this research show that there is a role of secure attachment for parents (mothers) in children which plays a role in the child's independence, there are children who have a secure attachment, namely self-confidence, feeling comfortable and caring. And there are factors that influence secure attachment, including affection. Attention, baby temperament, communication and conflict play an important role in children's independence. Based on 9 indicators of attachment and independence, namely as follows: love, attention, parental trust, communication, self-confidence, intrinsic and innovative motivation, accepting consequences of one's choice, being social and not being dependent in daily activities on the learning process. From the indicators, it can be seen from the results of observations and interviews that parents' secure attachment plays a very important role in children's independence at the Wolowa Baru Kindergarten.